Association of chronic kidney disease with impaired left atrial reservoir function: A community-based cohort study. (29th August 2020) - Nakanishi, Koki; Jin, Zhezhen; Russo, Cesare; Homma, Shunichi; Elkind, Mitchell SV; Rundek, Tatjana; Tugcu, Aylin; Sacco, Ralph L; Di Tullio, Marco R
Abstract: Background: Chronic kidney disease (CKD) is an independent risk factor for atrial fibrillation, although the pathophysiological mechanisms remain unclear. This study investigated the relationship between CKD and left atrial (LA) volume and function in a sample of the general population without overt cardiac disease. Design and methods: We examined 358 participants from the Cardiovascular Abnormalities and Brain Lesions study. The LA minimum volume index (LAVImin ), LA maximum volume index (LAVImax ), and LA emptying fraction (LAEF) were assessed by real-time three-dimensional echocardiography. Based on their estimated glomerular filtration rate (eGFR), the participants were divided into a CKD group (eGFR <60 ml/min/1.73 m 2 ) and a non-CKD group (eGFR ≥60 ml/min/1.73 m 2 ). Results: Of the 358 participants, 69 (19%) were classified as having CKD and 289 (81%) as non-CKD. Participants with CKD were older, had a greater prevalence of hypertension and use of antihypertensive drugs, a larger left ventricular (LV) mass index, and a higher prevalence of diastolic dysfunction than those without CKD (all p < 0.05). There was no significant difference in LAVImax between the CKD and non-CKD groups (23.4 ± 7.1 vs. 22.8 ± 5.8 ml/m 2, p = 0.47), whereas significant differences were observed for LAVImin (13.6 ± 5.5 vs. 12.0 ± 4.6 ml/m 2, p = 0.01) and LAEF (42.7 ± 11.4 vs. 47.8 ± 11.5%, p = 0.001). Multivariate regression analysis revealed that the eGFR was significantly associated with LAEF independent of age, LV mass index, and diastolic dysfunction (all p < 0.05). Conclusions: Participants with CKD in an unselected community-based cohort had significantly impaired LA reservoir function. Assessment of LA function may add important information in the prognostic assessment of patients with CKD even in the absence of overt cardiac disease.